Professional Development of Novice English Teacher in Junior High School - Mirizon, Soni; Anggraini, Fenisya; Inderawati, Rita (Jurnal Pendidikan Progresif, 2020)
Professional Development of Novice English Teacher in Junior High School. Objectives: This study aimed at finding out novice English teacher’s understanding about professional development in a junior high school in Palembang, novice teacher’s professional development, its challenges, how challenges are met, and supports provided by school and government. Methods: In this qualitative case study, the data were collected through questionnaires, interview, and documentation and were analyzed by using Likert Scale, transcription, codification, and thematic analysis. The participants were an English novice teacher, a senior teacher, and vice principle of curriculum affair. Findings: Regardless of her good understanding, the novice teacher lacked of professional development. She encountered instructional, social status and identity, classroom management and workload challenges, which were met by joining subject teachers’ forum, while advices and consent to join teachers’ forum were given as school support. Conclusion: Novice teacher should understand and apply professional development in her career.Keywords: professional development, novice teacher, English teacher.DOI: 10.23960/jpp.v10.i2.202009